The inner muses: How affective temperament traits, gender and age predict film genre preference. (August 2021) - Infortuna, Carmenrita; Battaglia, Fortunato; Freedberg, David; Mento, Carmela; Zoccali, Rocco Antonio; Muscatello, Maria Rosaria Anna; Bruno, Antonio
Abstract: The aim of this study is to assess whether different affective temperaments, age and gender are associated with specific film genre preference. An online survey was administered to 689 adult subjects. We assessed the film genre preference on a Likert scale and affective temperament traits using the self-report questionnaire Temperament Evaluation of Memphis, Pisa, Paris and San Diego (TEMPS-A) short-version scale. The scale showed acceptable psychometric properties. Results showed that cyclothymic temperament correlated positively with horror movie, depressive temperament correlated negatively with animation and positively with horror film, irritable temperament correlated negatively with animation and romance and positively with horror genre, hyperthymic trait correlated positively with comedy and musical genre, and anxious trait correlated negatively with documentary, thriller, action, and adult genres. Based on the population sampled, we concluded that stable, genetically conditioned styles of emotional reaction (temperaments) can predict film preference. Highlights: The individual factors that might influence film preference have still to be characterized. Gender, age and individual affective temperaments play important roles in film taste. Genetically conditioned styles of emotional reaction can predict film preference.